2012
DOI: 10.1186/1743-0003-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Interactive cueing with walk-Mate for Hemiparetic Stroke Rehabilitation

Abstract: BackgroundMany techniques that compensate for locomotion problems in daily life using externally controlled stimulation have recently been reported. These techniques are beneficial for effortlessly supporting patients’ locomotive functions, but the users of such devices must necessarily remain dependent on them. It is possible that some individuals with gait impairment may be prevented recovering locomotive function. From a rehabilitation viewpoint, it may therefore be supposed that ideally, devices that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…The present study differs from earlier studies [12, 1620] that used external feedback devices in two aspects: (1) auditory and/or somatosensory feedback used during real-time overground gait training and/or (2) outcome measures studied that included not only the temporal and clinical measures but also the spatial measures such as the COP trajectory and the peak pressure of the affected foot during gait. In addition, the modest improvement on clinical measures, TUG, FMA, and ABC strengthens our postulate that an intervention protocol aimed at increasing stance time and load on the affected side in stroke survivors ultimately results in better gait performance.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The present study differs from earlier studies [12, 1620] that used external feedback devices in two aspects: (1) auditory and/or somatosensory feedback used during real-time overground gait training and/or (2) outcome measures studied that included not only the temporal and clinical measures but also the spatial measures such as the COP trajectory and the peak pressure of the affected foot during gait. In addition, the modest improvement on clinical measures, TUG, FMA, and ABC strengthens our postulate that an intervention protocol aimed at increasing stance time and load on the affected side in stroke survivors ultimately results in better gait performance.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Muto et al used Walk-Mate device which is an acceleration sensor device that was worn on both ankles in individuals with stroke. It was capable of providing auditory feedback information on foot-ground contact [20]. Despite showing improvements in gait symmetry during the duration of training in stroke survivors, the improvements were not maintained immediately after training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using RAS showed increased gait speed and step length [27], and improved gait rhythm [28], but these studies focused on patients with hemiplegia and Parkinson's disease. To the best of our knowledge, the present study is the first to show the effect of RAS on the gait function of DPN patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, a decline in muscular power, balancing ability or cognitive function of aging humans decreases their walking ability. Some health problems, such as Parkinson's disease and unilateral paralysis from a stroke [23], can also cause a disorder that affects walking. These declines of walking ability increase the risk of falls and subsequently result in fall-related injuries [5].…”
Section: Introductionmentioning
confidence: 99%